Health impact of delayed implementation of cervical cancer screening programs in India: A modeling analysis. Issue 4 (16th October 2018) - Campos, Nicole G.; Tsu, Vivien; Jeronimo, Jose; Regan, Catherine; Resch, Stephen; Clark, Andrew; Sy, Stephen; Kim, Jane J.
Abstract : India has the highest burden of cervical cancer in the world. To estimate the consequences of delaying implementation of organized cervical cancer screening, we projected the avertable burden of disease under different implementation scenarios of a screening program. We used an individual‐based microsimulation model of human papillomavirus (HPV) infection and cervical cancer calibrated to epidemiologic data from India to project age‐specific cancer incidence and mortality reductions associated with screening (once‐in‐a‐lifetime among women aged 30–34 years) with one‐visit visual inspection with acetic acid (VIA) and one‐ and two‐visit HPV DNA testing. We then applied these reductions to a population model to project the lifetime cervical cancer cases and deaths averted under different implementation scenarios taking place from 2017 to 2026: (1) immediate implementation of screening with currently available screening tests (one‐visit VIA, two‐visit HPV testing); (2) immediate implementation of screening with currently available screening tests, with a switch to point‐of‐care one‐visit HPV testing in 5 years; and (3) 5‐year delayed implementation of screening with current screening tests or point‐of‐care HPV testing. Immediate implementation of two‐visit HPV testing with a switch to one‐visit HPV testing averted 574, 100 cases and 382, 500 deaths over the lifetimes of 81.4 million 30‐ to 34‐year‐old women screened once between 2017 and 2026. Delayed implementation with a one‐visit HPV test averted 209, 300 cases and 139, 100 deaths. Delaying implementation of screening programs in high‐burden settings will result in substantial morbidity and mortality among women beyond the age for adolescent HPV vaccination. Abstract : What's new? Nearly one‐quarter of cervical cancer cases worldwide occur in India. Nonetheless, while the disease can be prevented through screening for precancerous lesions, very few Indian women receive Pap tests. Here, the authors estimated cervical cancer burden in India assuming different screening program implementation scenarios, including immediate implementation with both one‐visit VIA and two‐visit human papillomavirus (HPV) testing and delayed implementation with a one‐visit HPV test. Models showed that immediate implementation of two‐visit HPV testing averted more than double the number of cases and deaths from cervical cancer among 30‐ to 34‐year‐old women compared with delayed implementation with one‐visit HPV testing.